Are Parents the Key to Preventing Unwanted Early Marriage Among Teenagers? : A Qualitative Study in Batangtoru District - Fauziah, Yaumil; Khairani, Fitri (Griya Widya: Journal of Sexual and Reproductive Health, 2024)
Background: Early marriage remains a significant public health and social issue in Indonesia, particularly among adolescents. In Batangtoru District alone, 32 cases of early marriage were reported in 2024. Early marriage is closely linked to negative consequences such as school dropout, maternal health complications, and increased risk of psychological issues. The role of parents is crucial in equipping adolescents with reproductive health knowledge and in supervising their relationships to prevent early marriage. Objective: This study aims to explore how parents fulfill their roles in preventing early marriage among adolescents in Batangtoru District, focusing on reproductive health education and monitoring of relationships with the opposite sex. Method: A qualitative research design with a phenomenological approach was employed. Data were collected through in-depth, semi-structured interviews with five adolescent informants aged 15–18 and five parent informants. Thematic analysis was used to identify patterns in parental involvement and its perceived impact. Results: The findings revealed that parents provided only limited reproductive health information, mostly restricted to menstruation and hygiene, and offered inconsistent supervision of adolescents’ interactions with the opposite sex. This lack of comprehensive education and structured oversight contributed to adolescents’ limited understanding of reproductive risks and allowed space for early sexual relationships, increasing the likelihood of early marriage. Conclusion: Parental roles in preventing early marriage remain underutilized due to limited knowledge, cultural taboos around sex education, and economic constraints. Strengthening family-based interventions, especially those that enhance parent-adolescent communication and reproductive health literacy, is essential for reducing the incidence of early marriage.